Plano Para a Uniformização da Nomenclatura das Intervenções na Boca - Bellizzi, Ataliba Macieira (2023)
Proposal for the uniformization of the nomenclature of oral operations. In the present paper the author presents a proposal for the uniformization of the nomenclature of oral operations-utilising the Greek prefixes and sufixes. Basing himself on available literature, he feels amply justified to do this in view of the great diversity of terms to designate the same operations. Furthermore, the denomination of the surgical act is completely confusing and does not give any idea of the extension of the operation. In addition to serious inconveniences of a technical order, an efficient Service of archives and statistics is completely impossible The author States that the classic writers follow the standard nomenclature, using prefixes (for the specific organs) and sufixes (for the specific operation), for the abdominal, pelvic and thoracic surgery. In the present paper the author presents prefixes and sufixes which can be used to describe oral operation. He follows a simple and easily understood norm. To conclude. the author emphasizes the necessity to refer to the access used (oral, through cervicotomy, prosotomy or cervicoprosotomy) according to the nature of the operation. so that the surgeon obtaines an more precise idea of the extension of the operative act.